2022
DOI: 10.1080/15548627.2022.2063003
|View full text |Cite
|
Sign up to set email alerts
|

Nucleoporin POM121 signals TFEB-mediated autophagy via activation of SIGMAR1/sigma-1 receptor chaperone by pridopidine

Abstract: Macroautophagy/autophagy is an essential process for cellular survival and is implicated in many diseases. A critical step in autophagy is the transport of the transcription factor TFEB from the cytosol into the nucleus, through the nuclear pore (NP) by KPNB1/importinβ1. In the C9orf72 subtype of amyotrophic lateral sclerosis-frontotemporal lobar degeneration (ALS-FTD), the hexanucleotide (G4C2)RNA expansion (HRE) disrupts the nucleocytoplasmic transport of TFEB, compromising autophagy. Here we show that a mol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 30 publications
(63 citation statements)
references
References 84 publications
(104 reference statements)
0
38
0
Order By: Relevance
“…In the presence of S1R antagonists (e.g., haloperidol, BD1047), the oligomeric forms predominate, whereas in the presence of S1R agonists (e.g., pentazocine, PRE-084), smaller sizes predominate [ 3 , 4 , 76 ]. Recent studies have elegantly demonstrated that S1R agonists and antagonists could be distinguished through non-denaturing PAGE (also known as native gel) followed by S1R immunoblotting [ 17 , 76 , 77 , 78 ]. Of note, even a lower-affinity S1R antagonist such as progesterone exhibited a strong oligomer-stabilizing effect [ 76 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In the presence of S1R antagonists (e.g., haloperidol, BD1047), the oligomeric forms predominate, whereas in the presence of S1R agonists (e.g., pentazocine, PRE-084), smaller sizes predominate [ 3 , 4 , 76 ]. Recent studies have elegantly demonstrated that S1R agonists and antagonists could be distinguished through non-denaturing PAGE (also known as native gel) followed by S1R immunoblotting [ 17 , 76 , 77 , 78 ]. Of note, even a lower-affinity S1R antagonist such as progesterone exhibited a strong oligomer-stabilizing effect [ 76 ].…”
Section: Resultsmentioning
confidence: 99%
“…However, the oligomer-destabilizing effect of lower-affinity putative S1R agonists (e.g., DHEA) could not be readily discerned [ 76 ]. Moreover, S1R oligomers on blots typically appear as a broad “smeary” band [ 17 , 76 , 77 ]. It is, thus, impractical to distinguish an S1R-specfic signal from “false-positive” background or S1R homomers from S1R heteromers complexed with other proteins.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nucleocytoplasmic transport has been reported to affect the translocation of MZF1 into the nucleus, inhibiting gene transcription in gliomas [ 4 ]. Approximately 30 nuclear nucleoporins (nuclear pore proteins) play an important role in nucleocytoplasmic transport [ 24 ]. Nevertheless, whether CTD inhibits nucleoporin expression to affect MZF1-regulated c-MYC transcription remains to be determined.…”
Section: Discussionmentioning
confidence: 99%
“…Autophagy is enhanced as the activation of SIGMAR1/S1R by pridopidine can chaperone the NP protein POM121, which recruits KPNB1 to transport TFEB into the nucleus. Therefore, pridopidine may ameliorate the TFEB transport deficit in the C9orf72 subtype of amyotrophic lateral sclerosis-frontotemporal lobar degeneration (ALS-FTD), where the mutation damages the nucleocytoplasmic transport of TFEB ( Wang et al, 2022 ). It has been approved as an orphan drug for ALS in the US and Europe.…”
Section: Drugsmentioning
confidence: 99%